Vascular Endothelial Growth Factor Receptor-1 Modulates Hypoxia-Mediated Endothelial Senescence and Cellular Membrane Stiffness via YAP-1 Pathways - Angom, Ramcharan Singh; Kulkarni, Tanmay; Wang, Enfeng; Kumar Dutta, Shamit; Bhattacharya, Santanu; Das, Pritam; Mukhopadhyay, Debabrata (Frontiers in Cell and Developmental Biology, 2022)
Hypoxia-induced endothelial cell (EC) dysfunction has been implicated as potential initiators of different pathogenesis, including Alzheimer's disease and vascular dementia. However, in-depth structural, mechanical, and molecular mechanisms leading to EC dysfunction and pathology need to be revealed. Here, we show that ECs exposed to hypoxic conditions readily enter a senescence phenotype. As expected, hypoxia upregulated the expression of vascular endothelial growth factor (VEGFs) and its receptors (VEGFRs) in the ECs. Interestingly, Knockdown of VEGFR-1 expression prior to hypoxia exposure prevented EC senescence, suggesting an important role of VEGFR-1 expression in the induction of EC senescence. Using atomic force microscopy, we showed that senescent ECs had a flattened cell morphology, decreased membrane ruffling, and increased membrane stiffness, demonstrating unique morphological and nanomechanical signatures. Furthermore, we show that hypoxia inhibited the Hippo pathway Yes-associated protein (YAP-1) expression and knockdown of YAP-1 induced senescence in the ECs, supporting a key role of YAP-1 expression in the induction of EC senescence. And importantly, VEGFR-1 Knockdown in the ECs modulated YAP-1 expression, suggesting a novel VEGFR-1-YAP-1 axis in the induction of hypoxia-mediated EC senescence. In conclusion, VEGFR-1 is overexpressed in ECs undergoing hypoxia-mediated senescence, and the knockdown of VEGFR-1 restores cellular structural and nanomechanical integrity by recovering YAP-1 expression.